Pro-health training and diet in selected disease entities - Wiesław Wojtanowski (University of Applied Sciences in Tarnow, Poland, 2021)
Healthy lifestyle, of which integral part is physical activity and proper diet, has an essential influence on the level of occurrence of various illnesses, as well as the length of human life. Positive aspects of physical activity include: removal of negative factors of contemporary life (stress, mental overload by intellectual work, hypokinesis), prevention the overload of motor organs and spinal pains, as well as diminution of the risk of occurrence of various illnesses like obesity, overpressure, atherosclerosis and diabetes. Besides, it toughens the organism and increases immunity. The diet of people who lead an active lifestyle should have high nutritive value, which means that it should provide proper quantity of energy mainly in form of carbohydrates (proper quantity of liquids with electrolytes is also very important). The main basis of every diet should be its diversity and balance. Besides, the diet must be adjusted to the treatment program of the disease. The aim of this dissertation is to present the influence of physical activity, pro-healthy exercises and proper diet on the treatment of the chosen diseases.